1992
DOI: 10.3109/00365529209000139
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Control of the Release of Somatostatin, Vasoactive Intestinal Polypeptide, Gastrin-Releasing Peptide, and HC1 from Porcine Non-Antral Stomach

Abstract: We studied the secretion of somatostatin and HCl and the release of vasoactive intestinal polypeptide (VIP) and gastrin-releasing peptide (GRP) from isolated, vascularly perfused, porcine non-antral stomach. Electric vagus stimulation increased acid secretion and the release of VIP and GRP and inhibited somatostatin secretion as determined in the venous effluent. Atropine abolished the HCl response and reversed the somatostatin inhibition to a three-fold increase, whereas GRP and VIP responses were unchanged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Results of some studies have strongly indicated involvement of intrinsic neurones (Schubert, 1991;Holst et al, 1992;Schubert et al, 1992;Welsh et al, 1994).…”
mentioning
confidence: 99%
“…Results of some studies have strongly indicated involvement of intrinsic neurones (Schubert, 1991;Holst et al, 1992;Schubert et al, 1992;Welsh et al, 1994).…”
mentioning
confidence: 99%
“…Tachykinins could thus, together with cholinergic and possibly gastrin‐releasing peptide neurones, be involved in the vagally mediated increase in acid secretion (Skak‐Nielsen et al . 1988, Holst et al . 1992, Lloyd & Debas 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We found that both SP and NKA are released by electrical stimulation of the vagus nerves and that they stimulated acid secretion. Tachykinins could thus, together with cholinergic and possibly gastrin-releasing peptide neurones, be involved in the vagally mediated increase in acid secretion (Skak-Nielsen et al 1988, Holst et al 1992, Lloyd & Debas 1994. Other results obtained in rats suggest that tachykininergic neurones in the spinal cord have inhibitory effects on vagally induced acid secretion (Okuma & Osumi 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations